Արդիականացման և իսլամի համատեղելիության հարցի շուրջ (Թուրքիայի մոդելը) - Բաղդասարյան, Սուրեն («Զանգակ - 97»)
At Lhe present limc in [he political and scientific circlcs of the West, as well as in the countrics of lhc Middlc East is discusscd the problcm of compatibility between the Islainic civilization's principles and values and the Western civilization's valuc system. As the niodcl of such a compatibility these circlcs often offer the examplc of 'furkey, which has scrvetl for the last fifty years as a "success story'՝ in the modernization of the Islamic socicty. therefore, the Turkish political experience can bc used in the implcmcnuition of "Grcater Middlc East" geopolilical projeet rcccntly dcclarcd by the U.S. administration.
Keywords: Պատմություն; Կրոն; Իսլամ